THE ANALYSIS OF THE ROLE OF THE AGRO-INDUSTRIAL SECTOR IN ECONOMISC: INTERNAL DEVELOPMENT AND FOREIGN TRADE - Tytarchuk , I.M. (The actual problems of regional economy development, 2020)
The main macroeconomic trends affecting the sector, the role of GDP in agriculture, forestry and fisheries, the features of public and private sectors in agriculture, the internal development of the agro-industrial sector by region and country, as well as the state of foreign trade and export prospects. . Particular attention is paid to state support for agriculture through budget funding of programs and its growth rate. From the point of view of the conceptual approach and the agreed methodology, the article describes the existing strategic and political priorities in the agro-industrial complex, its main achievements and significance. The review is a retrospective view aimed at performing an analysis with sufficient accuracy and sampling over the last five years. Existing special studies of the sector and official materials of statistical bodies and state organizations were used to deepen the understanding of the situation. On their main analysis of trends and changes in the role of the agro-industrial complex in the country's economy. Also, the survey identified the main obstacles faced by small and medium-sized enterprises in the agricultural sector in entering export markets. In accordance with the obtained results, practical advice for agricultural enterprises, public authorities and institutional organizations to support business development has been formed, which includes both new recommendations based on foreign experience and an improved mechanism for implementing already known tools. In particular, it is determined that the main areas of intervention of public and private institutions in the development of the agro-industrial complex should be the support of export operations (including their reduction in price) and the development of export support infrastructure (including regional). It is also proposed to take a more systematic approach to setting spending priorities together with increased predictability of funding, which will help make government support a more effective driver for sustainable development of the agro-industrial complex and GDP growth.